2021
DOI: 10.1051/e3sconf/202124001002
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and health risk assessment of trace elements inMytilus galloprovincialisas sea food in the Al Hoceima coasts (Morocco)

Abstract: The monthly variations in metal concentration of Cadmium (Cd), Zinc (Zn) and Chromium (Cr) were determined in tissues of Mytilus galloprovincialis and seawater obtained from the mussel farm installed along the Al Hoceima coasts, during the sampling period of 2018. The heavy metals encountered in the bivalves were higher than those observed in their environment with a decreasing order of Zn > Cr > Cd. The results also showed a decreasing trend for the metals studied during the summer sampling campaign. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
5
1
Order By: Relevance
“…Physicochemical parameters revealed significant variation according to seasons (Azizi et al, 2018(Azizi et al, , 2020(Azizi et al, , 2021Ngadi et al, 2021). These conditions are known to govern the bioavailability of contaminants (fecal indicator bacteria) in the marine environment and their bioaccumulation by marine biota (Darakas et Seasonal variations in the bacterial load in seawater, sediment and mollusks (Chamelea gallina) in the Ras Kabdana -Saidia area is illustrated in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Physicochemical parameters revealed significant variation according to seasons (Azizi et al, 2018(Azizi et al, , 2020(Azizi et al, , 2021Ngadi et al, 2021). These conditions are known to govern the bioavailability of contaminants (fecal indicator bacteria) in the marine environment and their bioaccumulation by marine biota (Darakas et Seasonal variations in the bacterial load in seawater, sediment and mollusks (Chamelea gallina) in the Ras Kabdana -Saidia area is illustrated in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Another probable reason for the high contents of fecal contaminations in Chamelia gallina in this period is likely the physiological status of the bivalve. Authors (Jozić et al, 2012;Skander et al, 2017;Hmeid et al, 2021) indicated that the biological status of the mussels is mainly regulated by the abiotic factors. During the rainy periods, the moderate temperature and/or the low salinity observed in the Ras Kebdana-Saîdia area promote the filtration rates in the bivalves and the animal can retain more fecal bacteria than other seasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of iron, copper, zinc, potassium, sodium, calcium, chloride, and lead were analyzed by atomic absorption spectrometry (model AFP100, Biotech Management Engineering Co. Ltd., Nicosia, Cyprus) [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a number of studies [ 19 , 20 , 21 , 22 , 23 , 24 ], the effect of the sampling site on trace element accumulation in mussels was investigated in the Mediterranean and Atlantic coastal areas. The trace element levels in soft tissues of M. galloprovincialis from different areas of the Black Sea also demonstrated significant spatial variability [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], especially for the animals of older age groups [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%